Policy experiments in an agent-based model with credit networks - Tiziana Assenza; Alberto Cardaci; Domenico Delli Gatti; Jakob Grazzini (Economics: The Open-Access, Open-Assessment E-Journal, 2018)
In this paper the authors extend the macroeconomic agent-based model described in Delli Gatti, D., Desiderio, S., Gaffeo, E., Cirillo, P. and Gallegati, M. (Macroeconomics from the bottom-up, 2011) with the inclusion of a bank-bank network that mimics real-world dynamics of interbank markets. They also introduce a public sector and other modifications in order to carry out different policy experiments. More specifically, they test the implementation of a monetary policy by means of a standard Taylor rule, an unconventional monetary policy (i.e. helicopter drop) and a set of macroprudential regulations. The authors explore the properties of the model for such different scenarios. The results shed some light on the effectiveness of monetary and macroprudential policies in an economy with an interbank market during times of crises.
Keywords: C63; E51; E52; 330; agent-based models; monetary policy; credit network